Non Dispersive Chemical Deacidification of Crude Palm Oil in Hollow Fiber Membrane Contactor - Mubiar Purwasasmita; Eryk Bone Pratama Nabu; K. Khoiruddin; I Gede Wenten (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
Performance of chemical deacidification of crude palm oil (CPO) using aqueous NaOH solution in a polysulfone hollow fiber ultrafiltration membrane was investigated. The effects of operating temperature, NaOH concentration and flow rates on percentage of free fatty acids (FFA) removal, oil loss, soap entrainment and overall mass transfer coefficient were evaluated. Overall mass transfer coefficients, soap content in oil and neutral oil loss all increased when the temperature was increased from 60 to 70°C due to an increase of the FFA distribution value. A minimum 0.25 N of NaOH or a NaOH to FFA molar ratio of about 7.62 was required to facilitate the expected extraction efficiency. The increased oil flowrate slightly enhanced the solute transport kinetics, while the aqueous phase flowrate did not significantly influence deacidification efficiency or mass transfer coefficient. About 97% of FFA removal was achieved within 4 hours. The maximum oil loss observed was 11% and the highest soap content in the oil without separation step was 3150 ppm. The values of the overall mass transfer coefficient varied from 2.97Ã—10-7 to 7.71Ã—10-7 m/s. These results show the potential of using the non dispersive membrane contacting process for chemical deacidification of CPO as well as other vegetable oils.